2022
DOI: 10.3390/ijerph19159220
|View full text |Cite
|
Sign up to set email alerts
|

Health Behavior Changes during the COVID-19 Pandemic: A Longitudinal Analysis among Children

Abstract: This longitudinal study compared children’s health behaviors before the COVID-19 pandemic versus during the pandemic. This analysis examined the association between individual-level characteristics and health behavior change. Four prospective cohort studies in the Environmental influences on Child Health Outcomes (ECHO) Program contributed data. Children aged 4–12 years and their caregivers were recruited in California, Colorado, North Dakota, and New Hampshire. Dietary intake, physical activity, screen time, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Children generally engaged in more sedentary ST before the pandemic than is recommended 30 and our data adds existing literature showing that this increased further during early months of pandemic restrictions 7,10,34,35 . Parents in our study reported that their children spent an average of 4 to 5 hours each day engaged in recreational ST, compared to a pre‐pandemic high of 154 ± 97.1 minutes/day shown by Burkart's team 7 .…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Children generally engaged in more sedentary ST before the pandemic than is recommended 30 and our data adds existing literature showing that this increased further during early months of pandemic restrictions 7,10,34,35 . Parents in our study reported that their children spent an average of 4 to 5 hours each day engaged in recreational ST, compared to a pre‐pandemic high of 154 ± 97.1 minutes/day shown by Burkart's team 7 .…”
Section: Discussionsupporting
confidence: 56%
“…Children generally engaged in more sedentary ST before the pandemic than is recommended 30 and our data adds existing literature showing that this increased further during early months of pandemic restrictions. 7,10,34,35 Parents in our study reported that their children spent an average of 4 to 5 hours each day engaged in recreational ST, compared to a prepandemic high of 154 ± 97.1 minutes/day shown by Burkart's team. 7 Children tended to engage in a bit more ST in the winter and summer than fall and spring, but no statistically significant differences were found by school group in either the cross-sectional or longitudinal samples.…”
Section: Discussionmentioning
confidence: 61%
“…Dates under study ranged from March 2018 (prepandemic reference) to April 2022 (during pandemic), although most studies collected data during January–December 2020. More information on characteristics of the studies can be found in Table 1 [ [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , ...…”
Section: Resultsmentioning
confidence: 99%
“…Majority of participants eating more small meals, compared with prior Parent-reported Dietary recall Bekelman et al. (2022) [ 40 ] 347 47% Female 4–12 y FFQ/questionnaire Quantity of food, SSBs, Discretionary food United States (0.92) July 2019–March 2021 No significant changes Self-reported and Parent-reported Prepandemic measurement (longitudinal) Weihrauch-Blüher et al. (2023) [ 41 ] 1004 52.3% Girls 3–17 y FFQ/questionnaire Eating more healthy Germany (0.94) March 2022–April 2022 Compared with before the pandemic, parents reported more children eating less healthy than more healthy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation